Can someone please help me with this?

f(x)=(x-2)^1/2 * (x^2-3)^3 find f'(x) using the product rul.

This is what I came up with I just need to know if I did it right.

f'(x)=(x-2)^1/2*3(x^2-3)+(x^2-3)^3*(1)^-1/2

Hopefully I did. Thanks.

no. You are not using the chain rule..

If f(x)=g(x) * h(x) then

f'(x)=g(x) * h'(x) + g'(x) * h(x)

now if h(x)= (x-2)^.5 then
h'(x) =.5 * (x-2)^-.5 *1

and if g(x)=(x^2-3)^3 then
g'(x)=3(x^2-3)^2 *(2x)

what is the product rule? Explain and provide an example

what is the product rule? Explain and provide an example

1 answer

Please help me with dis problem....
Y=(2-5x)^2